Tabela de composição de alimentos da Amazônia = Nutrient composition table for amazonian foods - Jaime Paiva Lopes Aguiar (My University, 2025)
The Amazon has long captivated the imagination. Since the earliest travellers ventured through it in the distant 16th and 17th centuries, the region has inspired admiration and wonder. Chroniclers, arriving from a Europe that had already been thoroughly mapped, were struck by the exuberance and incredible diversity of plants and animals that define the Amazonian landscape. For them, the New World posed both challenges and inspiration—fuel for the imagination and for scientific inquiry. This important work, now presented as a Nutritional Composition Table, is part of that rich and significant tradition. Its timely publication offers professionals in the field of human nutrition essential data to support and promote healthy and sustainable eating habits. The dissemination of such habits relies not only on appropriate public health policies but also on relevant research, such as the one documented in this publication. Moreover, it contributes to international efforts and aligns with FAO guidelines that advocate for the appreciation of local food species, biodiversity, and environmental sustainability. These are more than sufficient reasons for this presentation to be considered a well-deserved tribute to its author.
Keywords: Alimentos naturais - Amazônia; Segurança alimentar; Natural foods - Amazon; Food security